A Bibliometric analysis of green sukuk literature - Prayogo, Syamsi Mustofa Singgih; Raditya, Aji; Sarea, Adel (Center for Islamic Economics and Development Studies [P3EI], 2024)
Purpose – The objective of this study is to provide a comprehensive analysis of the current body of literature on green sukuk.Methodology – To achieve this objective, this study uses a bibliometric analysis and visualization and mapping of green sukuk research from to 2015-2023. The process of retrieving data through the Scopus database with the keywords